(untitled) (Third Sector Social Economic Review, 2022)
From public to private sector, environmentalist behaviors are on the agenda of all organizations. This environmentalist perspective, emphasized in many fields from education to economy, from politics to management, has become more visible in recent years. Green behavior has redefined in many areas of management. Institutions can consider green behaviors within the scope of social responsibility. Organizational reputation can be thought of as the sum of the perceptions that an organization has acquired over time and the future perceptions of that organization. In this study, it is investigated whether there is a relationship between green organizational behavior of teachers and organizational reputation. For this purpose, relational screening model and cluster sampling method were used. The Green Organizational Behavior Scale developed by Erbaşı (2019) and the Organizational Reputation Management Scale for Schools developed by Tümtürk (2020) were used in the study. 343 pieces of data were collected and analyzed with the help of SPSS program. According to the findings, teachers’ perceptions of green organizational behavior were found to be high, and their perceptions of organizational reputation were found to be low. There was no significant difference in gender, age, seniority, marital status, education level and branch variables for both variables. There is a positive moderate relationship between green organizational behavior and organizational reputation. Green organizational behavior and organizational reputation perceptions of teachers predict each other by 7.8%.